Comparison of Antiglycation and Antioxidant Potentials and Total Phenolic Contents of Decoctions from Antidiabetic Plants - Perera, P.R.D.; Ekanayake, S.; Ranaweera, K.K.D.S. (Procedia Chemistry, 2015)
Attached

N o n e n z y m a tic p ro te in g ly c a tio n a n d o x id a tiv e stress a re th e k e y m o le c u la r b a sis fo r th e m a c ro a n d m icro v a sc u la r c o m p lic a tio n s o b se rv e d in c h ro n ic d ia b etics. D e co ctio n s p re p a re d w ith m e d ic in a l p la n ts w ith an tig ly c a tio n a n d an tio x id a n t p o te n tia ls th e re fo re h a v e th e ra p e u tic p o te n tia l in p re v e n tin g d ia b e tic co m p lic a tio n s. D e co ctio n s o f fiv e an tid ia b etic p la n ts (p a rts) n a m e ly , Cassia auriculata flo w ers, Osbeckia octandra le av es, Syzygium cumini b a rk , Phyllanthus emblica fru its a n d Scoparia dulcis w h o le p la n t w e re a n a ly z e d fo r th e ir D P P H a n d A B T S a n tio x id a n t p o te n tia ls, an tig ly c a tio n p o te n tia ls a n d to ta l p h e n o lic co n te n ts. D ec o c tio n s o f S. cumini, O. octandra a n d P. emblica h a d sig n ific a n tly h ig h (p < 0 .0 5 ) a n tig ly c a tio n p o te n tia l ra n g e s o f 1 6 .8 - 3 5 .2 ,2 3 .0 -2 8 .5 a n d 3 7 .4 -8 2 .3 p g /m l w ith co rre sp o n d in g ly h ig h an tio x id a n t p o te n tia ls a n d to ta l p h e n o lic c o n te n ts o f 8 5 1 ,6 5 8 a n d 6 2 5 m g G A E /g resp ectiv ely .